2017
DOI: 10.3390/nu9030314
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot Juice Supplementation Improves High-Intensity Intermittent Type Exercise Performance in Trained Soccer Players

Abstract: It has been shown that nitrate supplementation can enhance endurance exercise performance. Recent work suggests that nitrate ingestion can also increase intermittent type exercise performance in recreational athletes. We hypothesized that six days of nitrate supplementation can improve high-intensity intermittent type exercise performance in trained soccer players. Thirty-two male soccer players (age: 23 ± 1 years, height: 181 ± 1 m, weight: 77 ± 1 kg, playing experience: 15.2 ± 0.5 years, playing in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 34 publications
9
76
3
3
Order By: Relevance
“…Our data indicate that acute BR supplementation has no effect on repeated sprint performance in adolescent males. Previous studies have shown that NO 3¯ supplementation consistently improved intermittent exercise performance over distances and durations associated with team sports athletes in match-play (Wylie et al 2013b;Thompson et al 2015;Thompson et al 2016;Nyakayiru et al 2017a). However, research investigating the effects of dietary NO 3¯ on maximal effort repeated sprint performance has not demonstrated clear benefits (Christensen et al 2013;Martin et al 2014;Wylie et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Our data indicate that acute BR supplementation has no effect on repeated sprint performance in adolescent males. Previous studies have shown that NO 3¯ supplementation consistently improved intermittent exercise performance over distances and durations associated with team sports athletes in match-play (Wylie et al 2013b;Thompson et al 2015;Thompson et al 2016;Nyakayiru et al 2017a). However, research investigating the effects of dietary NO 3¯ on maximal effort repeated sprint performance has not demonstrated clear benefits (Christensen et al 2013;Martin et al 2014;Wylie et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Beetroot juice (commercially available as Beet It shots, James White, UK) from a single batch was purchased from a local health‐food shop and sodium nitrate was purchased from Sigma‐Aldrich Australia (Sydney, NSW, Australia). Studies using Beet It doses of 70 mL report that each dose contains 400 mg nitrate, 21 mg betanin, 1.02 mg betaxanthin, and 22.6 mg total flavonoids (rutin equivalent) . C, C+B, and C+N rats were fed with C diet for the first 8 weeks and then with C, C + B or C + N diets for the last 8 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found ergogenic effects of nitrate supplementation when exercising under hypoxic conditions. This could be "local" tissue hypoxia, such as during anaerobic, highintensity intermittent exercise (Nyakayiru et al, 2017;Thompson et al, 2016;Wylie et al, 2013), or "systemic" normobaric/ hypobaric hypoxia (Carriker et al, 2016;Vanhatalo et al, 2010). Although "systemic hypoxia" has also been used with respect to maximal underwater exercise (Schagatay, 2010), the term "dynamic apnea" more appropriately reflects the different physiological characteristics associated with these breath-holding activities.…”
mentioning
confidence: 99%